Analysis of International Students’ Consumption Behavior：Evidence from EMU/TRNC - Ahemai, Adila (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study investigates the international students’ purchasing behavior in Eastern Mediterranean University (EMU), applying Chan’s (2005), the consumer behavior model. Consumer behavior is the study of when, why, how, and where people do or do not buy a product. It has sociological, psychological and economic dimensions and elements. It attempts to understand the consumer decision-making process, both individually and in groups (Jayaraj, 2017). Consumer behavior research is based on consumer buying behavior, with consumers playing the role of users, payers and buyers (Jayaraj, 2017). This study employed the constructs of demographic characteristics including age, gender, educational level, monthly income, length of residency in TRNC and nationality. This study also aimed to understand the international students’ consumer behavior in relation to promotion, product, price, quality, environmental characteristics, logistics, as well as, considering the online shopping behavior. For the purpose of this research, a survey questionnaire was administered to about 201 international students. The survey instrument contained demographic information and 31 measurement items. For the purpose of data analysis, SPSS (version 20.0.0) was utilized. The study revealed that international students’ consumer behavior is influenced by environmental characteristics, promotion, product, price, quality, logistics and access to online shopping. Study also revealed that different age groups are responding to the influencers differently. The gender differences, as the study showed, demonstrated different behavior in shopping decisions. The implications and limitations has also been discussed. Keywords: consumer behavior, international students, shopping decisions, environmental characteristics, promotion, product, price, quality, online shopping, logistics.

ÖZ: Bu çalışma, uluslararası öğrencilerin Doğu Akdeniz Üniversitesi'nde (DAÜ) satın alma davranışını araştırmakta ve tüketici davranışları modeli Chan'ı (2005) uygulamaktadır. Tüketici davranışı, insanların bir ürünü ne zaman, neden, nasıl ve nerede satın alıp almadıklarının incelenmesidir. Sosyolojik, psikolojik ve ekonomik boyutları ve unsurları vardır. Tüketici karar verme sürecini hem bireysel olarak hem de gruplar halinde anlamaya çalışır (Jayaraj, 2017). Tüketici davranışı araştırması, tüketicilerin kullanıcı, ödeme yapan ve alıcı rolünü üstlendiği tüketici satın alma davranışına dayanmaktadır (Jayaraj, 2017). Bu çalışmada, yaş, cinsiyet, eğitim düzeyi, aylık gelir, KKTC'de ikamet süresi ve uyruk dahil olmak üzere demografik özellikler yapıları kullanılmıştır. Bu çalışma aynı zamanda uluslararası öğrencilerin tüketici alışkanlıklarını promosyon, ürün, fiyat, kalite, çevresel özellikler, lojistik ve online satın alma davranışını göz önünde bulundurarak anlamaya yöneliktir. Bu araştırmanın amacı doğrultusunda, yaklaşık 201 uluslararası öğrenciye anket formu uygulanmıştır. Anket aracı demografik bilgiler ve 31 ölçüm maddesi içermektedir. Veri analizi amacıyla, SPSS (versiyon 20.0.) Kullanılmıştır. Çalışma, uluslararası öğrencilerin tüketici davranışlarının çevresel özellikler, tanıtım, ürün, fiyat, kalite, lojistik ve online alışverişe erişimden etkilendiğini ortaya koydu. Çalışma ayrıca, farklı yaş gruplarının etkileyenlere farklı şekilde tepki verdiğini ortaya koydu. Çalışmada görüldüğü gibi cinsiyet farklılıkları nakliye kararlarında farklı davranışlar sergilemiştir. Etkileri ve kısıtlamaları da tartışılmıştır. Anahtar Kelimeler: tüketici davranışı, uluslararası öğrenciler, nakliye kararları, çevresel özellikler, tanıtım, ürün, fiyat, kalite, online alışveriş, lojistik
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Habib Alipour.
Keywords: Tourism; International Students--Eastern Mediterranean University--Famagusta (Cyprus); Consumer behavior; international students; shopping decisions; environmental characteristics; promotion; product; price; quality; online shopping; logistics